Effects of strain rate and temperature on the mechanical properties of resin composites - Musanje, L.; Darvell, B.W. (Dental Materials, 2004)
To evaluate the effects of strain rate and temperature on the mechanical properties of resin composite restorative materials (RCs) and to investigate the construction of temperature—strain rate equivalence ‘master curves’. Four visible light-cured resin composite RCs, all of shade A3, were used: Heliomolar Radiopaque (HR) and Tetric Ceram (TC) (Ivoclar, Schaan, Liechtenstein), Filtek Z250 (FZ) (3M, St Paul, MN, USA) and Prodigy Condensable (PR) (Kerr, Orange, CA, USA). Bar specimens were cured for 50 s at an irradiance of 500 mW cm−2 and were randomly distributed into groups of six for each type of material. All specimens were stored in artificial saliva at pH 6, for 7 d. The specimens tested at 12, 24 and 37 °C were stored at the corresponding temperature but those tested at 0 °C were stored at 24 °C. Three-point bend tests for flexural strength (F), flexural modulus of elasticity (E) and total energy to failure (W) were performed at cross-head speeds (XHS) of 0.1, 1.0, 10, 50 and 100 mm min−1 for all materials as well as at 0.01, 0.03, 0.2 and 0.5 mm min−1 for some materials. There was a common pattern of behavior across materials. At constant temperature, F showed a slight variation with cross-head speed, with a broad peak in the region of 1–10 mm min−1. E, on the other hand, showed a more marked and steady increase with XHS at all temperatures except at 0 °C, where it tended to level off above about 10 mm min−1. In contrast, the values of W showed a decline with increasing XHS, except at 37 °C where an initial rise followed by a decline was observed. At constant XHS, increase in temperature caused a small, but highly significant (P<10−3) decline in F but a marked decline in E. W, again in contrast to F and E, showed a general increase with temperature. A master curve model for the temperature–strain-rate equivalence was fitted to the E and W data (all P<10−5) and the fitted parameters interpreted in terms of strain rate and temperature sensitivity.
Keywords: Standardization; Filled resin composite restorative materials; Modulus of elasticity; Strength